Aging male symptoms scale (AMS) for health-related quality of life in aging men: translation and adaptation in Malay - Hui, Meng Tan; Wah, Yun Low; Seng, Fah Tong; Haniff, Jamaiyah; Appannah, Geeta; Lee, Verna K. M.; Ee, Ming Khoo; Chirk, Jenn Ng; Chee, Christopher Kong Ho (Malaysian Public Health Physicians' Association, 2015)
The Aging Male Symptoms Scale (AMS) measures health-related quality of life in aging men. The objective of this paper is to describe the translation and validation of the AMS into Bahasa Melayu (BM). The original English version of the AMS was translated into BM by 2 translators to produce BM1 and BM2, and subsequently harmonized to produce BM3. Two other independent translators, blinded to the English version, back-translated BM3 to yield E2 and E3. All versions (BM1, BM2, BM3, E2, E3) were compared with the English version. The BM pre-final version was produced, and pre-tested in 8 participants. Proportion Agreement, Weighted Kappa, Spearman Rank Correlation Coefficient, and verbatim responses were used. The English and the BM versions showed excellent equivalence (weighted Kappa and Spearman Rank Coefficients, ranged from 0.72 to 1.00, and Proportion Agreement values ranged from 75.0% to 100%). In conclusion, the BM version of the AMS was successfully translated and adapted.